2007
DOI: 10.1038/modpathol.3800763
|View full text |Cite
|
Sign up to set email alerts
|

Fascin overexpression in intraductal papillary mucinous neoplasms (adenomas, borderline neoplasms, and carcinomas) of the pancreas, correlated with increased histological grade

Abstract: Intraductal papillary mucinous neoplasm (IPMN) is a well-established entity in pancreatic neoplasms and a precursor of infiltrating adenocarcinoma. Fascin, an actin-bundling protein involved in cellular motility, is upregulated in many human neoplasms. Its overexpression in pancreatic intraepithelial neoplasia, a precancerous lesion sharing many characteristics with IPMN, has been reported. However, fascin expression in IPMN remains unknown. The aim of this study was to investigate fascin expression in IPMNs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 44 publications
3
35
0
1
Order By: Relevance
“…23 Although fascin-1 expression is absent or very low in the normal epithelium, it is upregulated in several types of carcinomas, including those of the lung, esophagus, stomach, colon, pancreas and urinary bladder. [24][25][26][27][28][29] Furthermore, overexpression of fascin-1 is correlated with worse prognosis and metastasis in several types of carcinomas. [25][26][27] The role of fascin-1 in carcinomas also has been probed experimentally in cell lines and mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…23 Although fascin-1 expression is absent or very low in the normal epithelium, it is upregulated in several types of carcinomas, including those of the lung, esophagus, stomach, colon, pancreas and urinary bladder. [24][25][26][27][28][29] Furthermore, overexpression of fascin-1 is correlated with worse prognosis and metastasis in several types of carcinomas. [25][26][27] The role of fascin-1 in carcinomas also has been probed experimentally in cell lines and mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…One in vitro study revealed that all 33 ESCC cell lines expressed fascin protein at a certain level, and down-regulation of fascin expression reduced the motile and invasive properties in a fascin-overexpressed cell line (3). Fascin overexpression was positively linked to invasion, metastasis or staging in oral squamous, esophageal, colorectal, pancreatic and renal cell carcinoma at the level of protein or mRNA (3,13,(24)(25)(26). Moreover, ki-67, present in the nuclei of cells in the G 1 , S and G 2 phases of the cell cycle as well as in mitosis (27), was found to be highly expressed in fascin-positive areas, compared with fascinnegative areas (28).…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…In vitro experimental evidence indicated that fascin overexpression correlated with increased proliferation, altered ß1 integrin distribution, enhanced invasive capacity and an altered differentiation status in colonic adenocarcinoma (12). Up-regulated fascin induces a high potential for invasion and metastasis in various malignancies, including carcinomas of the pancreas, lung, esophagus and breast (3,8,13,14).…”
Section: Introductionmentioning
confidence: 99%
“…It was named fascin because of its ability to form tight and stable bundles with F-actin (Kureishy et al 2002). Fascin is absent or shows very low expression in normal epithelium but is upregulated in transformed cells and in many kinds of human neoplasms, such as esophageal (Hashimoto et al 2005;Xue et al 2006), gastric (Hashimoto et al 2004), colonic (Hashimoto et al 2006), pancreatic (Yamaguchi et al 2007), lung (Pelosi et al 2003), breast (Rodríguez-Pinilla et al 2006), ovarian (Daponte et al 2008), prostate (Darnel et al 2009), and thyroid (Chen et al 2008) tumors, and high expression of fascin is associated with poor survival of patients.…”
mentioning
confidence: 99%